Occurrence of Fe3+ and formation process of precipitates within oxidized olivine phenocrysts in basalt lava from Kuroshima volcano, Goto islands, Nagasaki, Japan. (2nd January 2018) - Ejima, T.; Akasaka, M.; Nagao, T.; Ohfuji, H.
Abstract: The oxidation state of Fe and precipitates within olivine phenocrysts from an olivine-basalt from Kuroshima volcano, Goto Islands, Nagasaki Prefecture, Japan, were determined using electron microprobe analysis, 57Fe Mössbauer spectroscopy, Raman spectroscopy and transmission electron microscopy, to examine the formation process of the Fe-bearing precipitates. The average Fo content of the olivine phenocrysts is 76.2 mol.%. The olivine phenocrysts occasionally have precipitate minerals at their rims, especially on rims near vesicles. The57 Fe Mössbauer spectrum of olivine separates consists of two doublets assigned to Fe 2+ at the octahedral M1 and M2 sites, and a Fe3+ doublet at the M1 and M2 sites. The Fe 2+ :Fe 3+ ratio is 90(5):10(1). The precipitates at the rims of the olivine phenocrysts consistof magnetite and enstatite showing coaxial relations with host olivine, and grow parallel to the olivine c axis. Moreover, clusters consisting of nanoscale domains of a few tens of nm in size occur in the host olivine. Their rounded form and appearance in transmission electron microscope images are similar to those of the magnetite precipitates, but they have an olivine structure and can be regarded as embryos of magnetite within the olivine. The oxidation process of olivine phenocrysts under cooling conditions is: (1) formation of magnetite embryos on the rims of olivinephenocrysts; (2) formation of enstatite-like pyroxene domains by depletion of Fe in olivine due to the generation of magnetite embryos; (3) crystallization of magnetite and enstatite-like pyroxene precipitates.